About generation of subharmonics and stochatic regimes arising in periodic plasma-filled waveguides excited by charged beam - Babaskin, A.A.; Kirichok, A.V.; Kuklin, V.М.; Mouharov, S.Т.; Zaginajlov, G.I. (Вопросы атомной науки и техники, 2000)
Various mechanisms for generation of subharmonics in periodic plasma-filled waveguides excited by charged beam are considered. It is shown that beam particles seized by the excited electromagnetic wave can demonstrate under certain conditions the complex dynamics that results in generation of subharmonics and cause the transition to the stochastic regime of the instability.